Răspuns :
a) a²(a+2)-4(a+2)=(a+2)(a²-4)=(a+2)(a-2)(a+2)
b)9x²+12x+4-4x²=5x²+12x+4
c)9(x+2)²-(2x-1)²=9(x²+4x+4)-(4x²-4x+1)= 9x²+36x+36-4x²+4x-1=5x²+40x+35=5(x²+8x+7)=5(x+7)(x+1)
d) (x+2)²-(2x-1)²=x²+4x+4-(4x²-4x+1)= -3x²-3=-3(x²+1)
Voi folosii formula : a²-b² = (a+b)(a-b) !
a) ... exercitiul =a²(a+2)-4(a+2)=(x+2)(a²-4)=(a+2)(a+2)(a-2)=(a-2)(a+2)² ;
b) ... exercitiul =(3x+2 + 2x)(3x+2 - 2x)=(5x+2)(x+2) ;
c) ...=exercitiul =(3x+6 + 4)(3x+6 - 4) = {3x+10)(3x+2) ;
d) ...=exercitiul =(x+2 + 2x-1)(x+2 - 2x+1)=(3x+1)(-x+3) ;
a) ... exercitiul =a²(a+2)-4(a+2)=(x+2)(a²-4)=(a+2)(a+2)(a-2)=(a-2)(a+2)² ;
b) ... exercitiul =(3x+2 + 2x)(3x+2 - 2x)=(5x+2)(x+2) ;
c) ...=exercitiul =(3x+6 + 4)(3x+6 - 4) = {3x+10)(3x+2) ;
d) ...=exercitiul =(x+2 + 2x-1)(x+2 - 2x+1)=(3x+1)(-x+3) ;